IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 1 TAHUN 2010 TENTANG RETRBUSI IZIN MENDIRIKAN BANGUNAN - Yuda Ariandi; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Implementation of Pekanbaru City Regional Regulation No. 1 Year 2010 About Levy Building Permit. Currently construction in Pekanbaru City alone more rapidly, as seen in the many development shops, homes, shops, and others. of the many development there are deviations from the development plan on which the IMB administration did not even have a building permit. For the implementation of the Regional Regulation No. 1 Year 2010 About the Building Permits, the government has set the Pekanbaru City Planning Office Building for running various authorities in order to achieve the objectives of these regulations.Based on the above problems, as for the formulation of the issues raised is How Pekanbaru City Regional Implementation Regulation No. 1 of 2010 on Building Permits in the District Charming? The type of research in the study were included into the type of qualitative research by using descriptive survey method. Who became informants in this study is the Head of Department of Spatial Planning and Building Pekanbaru, Section of Supervision and Control Building and communities with building permit / do not have building permits in Pekanbaru, especially in the district of handsome 5 people.From interviews conducted by the author to the respondents it can be concluded as follows LGs in disseminating this policy through sosialisaidan extension directly, the clarity of the information to which there are still many people who do not understand well the clarity of the sanctions contained in the policy Retribution IMB, Resources in the implementation of policy in the field the quantity is still inadequate, employee placement implementers in the field in this field officers and field supervisors are in accordance with the field and spesealisasinya and bureaucratic structure that forms of coordination and cooperation among the parties involved in the implementation of public policies such as IMB retribution for field workers. Obstacles in the Implementation of Regional Regulation No. 1 Year 2010 Pekanbaru About Permits Building in District Charming is the Number of inspectors from the Department of Spatial Planning and Building inadequate, limited operational vehicles as well as the lack of public awareness for the care of IMB.Keywords : Implementation, Building, Levy Building Permits